Pharmacoeconomic Rationale of Zinc Supplementation In The Management of Acute Diarrhea In Children With Rotavirus Infection In Indonesia - Mohamad Saifudin Hakim; Serhii Soloviov; Yati Soenarto; Iryna Dzyublyk; Maryia Leleka; Viktor Trokhymchuk (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2019)
Rotavirus is one of the most important causative agents of gastroenteritis in both infants and children worldwide, resulting in a high mortality and burden of disease, mainly in low-income, developing countries. Oral rehydration therapy with zinc supplementation is currently the recommended way to prevent death from diarrheal dehydration. In this study, we aimed to estimate the effectiveness of zinc supplementation in combination therapy of patients with suspected rotavirus infection in Indonesia. The perspective of this pharmacoeconomic study refer to the economic vantage point of cost-of-illness analysis. Achievement of this goal was possible with the construction of a decision tree model and determination of decision rules for inclusion of zinc supplementation into the combination therapy. The input parameters of the model were hospitalization days of patients stratified by the presence or absence of rotavirus infection as well as the additional inclusion of zinc supplementation. The criterion for prediction and decision making was the global rotavirus prevalence. The feature of the simulation was that the costs were expressed as relative to each other, which allowed to unify the proposed methodology. Retrospective analysis of clinical database of Indonesian patients with acute diarrhea has shown that zinc supplementation would be rational in case of rotavirus prevalence among these patients is higher than 81.5%. It was shown that additional zinc supplementation would be costeffective with probability of 0.62 and 0.53 – in the positive range of cost ratio variation or if costs for less than 43% of baseline therapy per day costs on an average.